PERBANDINGAN SISTEM HUKUM COMMON LAW, CIVIL LAW DAN ISLAMIC LAW DALAM PERSPEKTIF SEJARAH DAN KARAKTERISTIK BERPIKIR - Aulia, Farihan; Al-Fatih, Sholahuddin (Faculty of Law, University of Muhammadiyah Malang, 2017)
The legal system or commonly referred to as the legal tradition, has a wealth of scientific treasures that can be examined in more depth through a holistic and comprehensive comparative process. Exactly, the comparison of the legal system must accommodate at least three legal systems that are widely used by countries in the world today. The three legal systems are the Continental European legal system, Anglo American and Islamic Law. The comparative study of the three types of legal systems found that the history of the Continental European legal system is divided into 6 phases, while Anglo American legal history began in the feudalistic era of England until it developed into America and continues to be studied until now. Meanwhile, the history of Islamic law is divided into 5 phases, starting from the Phase of the Prophet Muhammad to the Resurrection Phase (19th century until nowadays). In addition to history, the authors find that the Continental European legal system has the characteristic of anti-formalism thinking, while the Anglo American legal thinking characteristic tends to be formalism and is based on a relatively primitive mindset. While the thinking character of Islamic Law is much influenced by the thought of the fuqoha (fiqh experts) in determining the law to solve a problem, so relatively dynamic and moderate.